International Marketing: Problems and Prospects in Modern Economy Development ("Journal "U". Economy. Management. Finance.", 2017)
The article considers the concept of international marketing, its importance for development of world business community and integration into a general enterprise management system. The research determines the main problems of international marketing, and also tendencies for its development in Russia and abroad.
Keywords: international marketing; marketing; globalization of economy